The Impact of ICT on Financial Development: Evidence from Southeast Asian Countries - Minh, Nguyen Hoang (VNU JOURNAL OF ECONOMICS AND BUSINESS; Vol 2 No 5, 2022)
This article aims to analyze the impact of Information & Communication Technologies (ICT) on financial development in several Southeast Asian countries (Vietnam, Singapore, Thailand, Indonesia, Malaysia, Brunei, and the Philippines) from 1996 to 2019. Data in this study are collected from the World Bank (World Bank), the International Monetary Fund (IMF), and the Pooled-OLS, random-effects, fixed-effects, and Driscoll-Kraay estimation methods are used. The research results show that ICT has a positive impact on the financial development of some Southeast Asian countries. Based on the research results, some Southeast Asian countries need to have appropriate policies for increasing financial development through ICT.